Did Botswana Escape from the Resource Curse? - Iimi, Atsushi (IMF Working Papers; Working Paper, 2006)
Botswana is typical of the countries that are endowed with abundant natural resources. Although it is commonly accepted that resource-rich economies tend to fail in accelerating growth, Botswana has experienced the most remarkable economic performance in the region. Using the latest cross-country data, this study empirically readdresses the question of whether resource abundance can contribute to growth. It finds that governance determines the extent to which the growth effects of resource wealth can materialize. In developing countries in particular, the quality of regulation, such as the predictability of changes of regulations, and anticorruption policies, such as transparency and accountability in the public sector, are most important for effective natural resource management and growth.